Analisis Culture Shock di Lingkungan Baru terhadap Tingkat Stress pada Mahasiswa Perantau - Muhamad Akmal Wahyu Andhika; Deni Deni; Muhammad Iman Nurul Nazid; Sri Mulyeni (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This research aims to explore a culture shock phenomenon and its impact on the stress levels and adaptation processes of migrant students at PASIM national University, as individuals who move into a new environment, culture, different geographical features, migrant students often face problems in communication or psychological pressure. Data collected process done by interviewing respondents, thru qualitative method with phenomenological approach to deeply describe life experiences. Basically culture shock has four phases, start with initial disorientation and cognitive load due to the uncertainty of social life, followed by emotional pressure leading to social isolation and homesickness. After those two the adaptive coping process activated starting with building relationships with peers, after all of these phases formed the increase of post-crisis increase in intercultural and social competence. This finding indicate that early phase of culture shock does indeed have a negative impct, however, as the adaptation process an individual can develop an independence dan stronger self-identity. Conclusion, this research emphasizes the importance of internal resilience and the support external support in transforming challenges into opportunities for self-development that can lead to personal growth and benefits.